2015
DOI: 10.1530/rep-14-0576
|View full text |Cite
|
Sign up to set email alerts
|

Regeneration of Leydig cells in ectopically autografted adult mouse testes

Abstract: Ectopic autografting of testis tissue is a promising approach for studying testicular development, male germline preservation and restoration of male fertility. In this study, we examined the fate of various testicular cells in adult mouse testes following ectopic autografting at 1, 2, 4 and 8 weeks post grafting. Histological examination showed no evidence of re-establishment of spermatogenesis in autografts, and progressive degeneration of seminiferous tubules was detected. Expression of germ cell-specific p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
11
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 60 publications
(73 reference statements)
2
11
1
Order By: Relevance
“…The inability of xenografts from adult testis to produce sufficient testosterone could be due to lack of mature Leydig cells. These results contradict previous findings where restoration of seminal vesicle weight in mice 26, 27 and, serum testosterone level in rats 28 following adult testis autografting has been reported. This inconsistency could be due to failure or delay in the establishment of angiogenesis in xenografted adult testis leading to loss of Leydig cells 29 .…”
Section: Resultscontrasting
confidence: 97%
See 2 more Smart Citations
“…The inability of xenografts from adult testis to produce sufficient testosterone could be due to lack of mature Leydig cells. These results contradict previous findings where restoration of seminal vesicle weight in mice 26, 27 and, serum testosterone level in rats 28 following adult testis autografting has been reported. This inconsistency could be due to failure or delay in the establishment of angiogenesis in xenografted adult testis leading to loss of Leydig cells 29 .…”
Section: Resultscontrasting
confidence: 97%
“…It is likely that spermatozoa being terminally differentiated cells are rather resistant to degeneration and are able to survive in degenerated tubules. We had observed similar findings in autografted adult mice testis 27 and another report also confirmed similar finding 16 . Testis from immature donors could establish spermatogenesis following ectopic xenografting and meiosis was induced as indicated by the presence of pachytene-stage spermatocytes as the most advanced germ cells (Fig.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Heterotopic transplantation showed signs of testicular structure disintegration and extensive seminiferous tubules degeneration, except for one sample where it was possible to identify intact seminiferous tubules. Obtained data corroborates with Makala et al . (2015) results, showing that when autologously transplanting testicular fragments (5mm) on the back of adult mice, there was an extensive seminiferous tubule degeneration 4 weeks after grafting and no intact seminiferous tubule present after 8 weeks.…”
Section: Discussionsupporting
confidence: 91%
“…The testis is not only responsible for spermatogenesis, but also for sex hormone production in animals. Several attempts using zebrafish, mice, and pigs for the characterization of testis regeneration revealed limited spermatogenic or steroidogenic functions, except in newborn animals [ 6 , 7 , 8 ]. Similarly, studies by Song and Silversides (2007) [ 9 ] reported that hetero-transplanted testicular slices from a newly hatched chick into a recipient chick’s abdomen were able to grow and produce functional sperm that generated donor-derived progeny, which suggested that chicken testes have a strong regenerative potential.…”
mentioning
confidence: 99%